Application of Computer Vision to image review process in the software development - Marques, Wendell; Bonfim, Andrezza De Melo; Filho, Eduardo; Veras, Edluce Leitao; Souza, Daniel; Silva, Vinicius Gabriel da (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2025: Anais do X Simpósio Brasileiro de Testes de Software Sistemático e AutomatizadoDO - 10.5753/sast.2025.13969, 2025)
The main goal of reviews in software development is to grant the quality and correctness of the products. One of those tasks that we can highlight is image review. This process could require more time to process and tends to be less accurate due to human error. Considering that developers who perform this type of task also have other responsibilities, the longer the review takes, the more work time is required, and this can affect the time of deliverables in the industry. Therefore, the proposal of this research is to use Optical Character Recognition (OCR) and Computer Vision (CV), to automate the process of image review, for the interpretation and validation of the content, both textual and objects. To carry out this research a set of 100 images was used in manual and automated review process and was verified that the automated approach reduced the execution time by 96.45%, and reduced the number of errors by 4%, proving that it is feasible in this development context. The application of this tool helped to increase efficiency by reducing the time spent on manual reviews, increased the consistency of image analysis, ensuring better accuracy compared to manual reviews. It also promoted improvements in development and the team, through a more productive work environment.